Histological Structure of the Vascular layer and the Retina layer of Eye in Iraqi blacked partridge Francolinus francolinus (Linnaeus,1766) - Ahmed , Ahmed Mustafa; Mahdi, Mohammed A . (American Journal of Bioscience and Clinical Integrity, 2026)
Objective :The present study aimed to identify the histological structure of the vascular layer and retina layer in the eye of the Iraqi blacked partridge Francolinus francolinus . Methods : Using five adult birds samples, 10% formalin solution was used to anesthetize the animals, anatomicize the samples, and perform a number of histological staining procedures. Results : The choroid, ciliary body, and iris are the three components that make up the vascular layer of the eye. The choroid is loose, vascularized connective tissue, and also contains many pigment cells, and consists of several layers including , Epichoroid lamina , choriocapillary layer and Bruch’s membrane. the ciliary body, which was attached anteriorly to the iris, served as the choroid’s anterior support structure. The ciliary body encompassed the stroma, epithelium, and smooth muscles fibers .The ciliary epithelium consisted of two cell layers. The nonpigmented innermost section of the epithelium. A pigmented outer ciliary epithelium connected to the pigmented retinal epithelium.The stroma is ahighly ,vascularized ,loose connective tissue layer, situated between the ciliary muscle and the epithelial layer ,directly continous with iris stroma anteriorly and choroid posteriorly, it contains blood vessels ,fibroblasts ,and pigmented cells .The iris’s anterior surface is covered with a thick layer of Pigmented cells and fibroblasts. The stroma contained blood vessels, smooth muscles, whereas the two layers of epithelium protecting the ciliary processes are continuous on the posterior surface..The retina consisted of two parts: a nonsensory region and a sensory section. The retina’s ten layers made up its sensory portion: first layer is the epithelium ant it is called retinal pigmented , second layer is rods and cones , the third layer is the membrane which is called external limiting , the fourth layer is external nuclear, the fifth layer is called external plexiform , the sixth layer , which is called internal nuclear, and seventh in the arrangement of the layers of the retina is called internal inner plexiform , the eighth layer of the retina is ganglion cell , the ninth layer is called nerve fibers, finally inner limiting membrane